A Small‐Molecule Fluorescence Probe for Nuclear ATP. Issue 15 (1st March 2023) - Tamima, Umme; Sarkar, Sourav; Islam, Md Reyazul; Shil, Anushree; Kim, Kyeong Hwan; Reo, Ye Jin; Jun, Yong Woong; Banna, Hasanul; Lee, Soobin; Ahn, Kyo Han
Abstract: Fluorescence monitoring of ATP in different organelles is now feasible with a few biosensors developed, which, however, show low sensitivity, limited biocompatibility, and accessibility. Small‐molecule ATP probes that alleviate those limitations thus have received much attention recently, leading to a few ATP probes that target several organelles except for the nucleus. We disclose the first small‐molecule probe that selectively detects nuclear ATP through reversible binding, with 25‐fold fluorescence enhancement at pH 7.4 and excellent selectivity against various biologically relevant species. Using the probe, we observed 2.1–3.3‐fold and 3.9–7.8‐fold higher nuclear ATP levels in cancerous cell lines and tumor tissues compared with normal cell lines and tissues, respectively, which are explained by the higher nuclear ATP level in the mitosis phase. The probe has great potential for studying nuclear ATP‐associated biology. Abstract : The first small‐molecule probe for nuclear ATP is reported. The probe, a Zn II complex of a push‐full type benzocoumarin dye bearing a dipicolylamine ligand, reversibly binds to nuclear ATP with a turn‐on fluorescence response. Using the probe, we observed markedly higher levels of nuclear ATP in organ tissues of a tumor‐xenografted mouse by two‐photon microscopy, which is ascribed to aggressive cell progression in the mitosis phase.